Prevalence of Resistant Strains of Streptococcus Pneumoniae to Oxacillin, Ofloxacin and Rifampicin in Abraka South-South Nigeria (Global Journal of Medical Research, 2015)
The clinical isolate Streptococcus pneumoniae is a major cause of illness such as pneumoniae, meningitis, bacteremia and otitis media in children and the elderly. The emergence of drug-resistant strains threatens to complicate the management of these diseases. An hospitalbased and community-based surveillance for drug-resistant Streptococcus pneumoniae in outpatients with respiratory infection in Abraka, Delta State Nigeria was conducted. Between August -October 2014, a cross-sectional study was conducted in Abraka general hospital and Abraka community to assess the prevalence of drug resistant Streptococcus pneumoniae isolated from sputum samples of patients with cough and catarrh (respiratory tract infection). A total of 125 sputum samples of patients with respiratory tract infection were collected and inoculated on 5% sheep-blood agar, incubated at 35oC for 24hours in 5-10% CO2. Susceptibility testing panels of Ofloxacin, Rifampicin and Oxacillin were tested against isolated Streptococcus pneumoniae. Of the 125 sputum samples collected 28 (22.4%) was positive for Streptococcus pneumoniae.
Keywords: pneumonia; resistance; susceptibility; prevalence